The Sheep as a Comprehensive Animal Model to Investigate Interdependent Physiological Pressure Propagation and Multiparameter Influence on Cerebrospinal Fluid Dynamics - Trimmel, Nina Eva; Podgoršak, Anthony; Oertel, Markus Florian; Jucker, Simone; Arras, Margarete; Schmid Daners, Marianne; Weisskopf, Miriam (Frontiers in Neuroscience, 2022)
The present study aims to develop a suitable animal model for evaluating the physiological interactions between cerebrospinal fluid (CSF) dynamics, hemodynamics, and abdominal compartment pressures. We seek to contribute to the enhanced recognition of the pathophysiology of CSF-dependent neurological disorders like hydrocephalus and the improvement of available treatment options. To date, no comprehensive animal model of CSF dynamics exists, and establishing an accurate model will advance our understanding of complex CSF physiology. Persisting knowledge gaps surrounding the communication and pressure propagation between the cerebrospinal space and adjacent anatomical compartments exacerbate the development of novel therapies for neurological diseases. Hence, the need for further investigation of the interactions of vascular, craniospinal, and abdominal pressures remains beyond dispute. Moreover, the results of this animal study support the optimization of in-vitro test benches for medical device development, e.g., ventriculoperitoneal shunts. Six female white alpine sheep were surgically equipped with pressure sensors to investigate the physiological values of intracranial, intrathecal, arterial, central venous, jugular venous, vesical pressure, and four differently located abdominal pressures. These values were measured simultaneously during the acute animal trial with sheep under general anesthesia. Both carotid and femoral arterial blood pressure indicate a reliable and comparable representation of the systematic blood pressure. However, the jugular venous pressure and the central venous pressure in sheep in dorsal recumbency do not correlate well under general anesthesia. Furthermore, there is a trend for possible comparability of lateral intraventricular and lumbar intrathecal pressure. Nevertheless, animal body position during measurements must be considered since different body constitutions can alter the horizontal line between the cerebral ventricles and the lumbar subarachnoid space. While intra-abdominal pressure measurement in the four different abdominal quadrants yielded greater inter-individual variability, intra-vesical pressure measurements in our setting delivered comparable values for all sheep. We established a novel and comprehensive ovine animal model to investigate interdependent physiologic pressure propagation and multiparameter influences on CSF dynamics. The results of this study will contribute to further in-vitro bench testing, the derivation of novel quantitative models, and the development of a pathologic ovine hydrocephalus model.